THE APPLICATION OF THE CONCEPT OF ECO GREEN-TOURISM IN DEVELOPING THE TOURIST VILLAGE THROUGH THE LOW IMPACT DEVELOPMENT - Wiwik Setyaningsih; Tri Yuni Iswati; Sri Yuliani (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
The concept of green eco-tourism is a concept of regional development for environmentally sustainable tourism activities. Tourism activities have a significant effect on the development and improvement of the economic, social, cultural sectors and the quality of the surrounding environment which subsequently causes the global issue of World Tourism Organization (WTO) to emerge. It is then relevant to apply the concept of eco-green tourism in developing the strategic areas intended for tourism in line with the program of the government of Surakarta city which aims at developing the city within the concept of eco-culture city.Some tourist villages (kampung wisata) with local wisdom potentials as the historical areas in Surakarta city are still not handled optimally. This trend can be seen in some of areas which have begun to lose their original characteristics and have even changed function. This phenomenon will slowly and certainly erode the local wisdoms of the historical villages which will eventually cause the unique characteristics as the local potentials of the city to disappear. Therefore, one of the right and integrated actions to handle such a problem is the research model of development of the tourist villages through LID (Low Impact Development) by having the concept of eco-green tourism.The objective of this research is to formulate the model of development of the tourist villages through LID (Low Impact Development) in bringing eco-green tourism into reality. This formulation is based on descriptive explorative method. This research was conducted in the historical area of Kauman tourist village which still has the authenticity of potentials of the value of characteristics of high local wisdoms which are still in existence and development.The results of this research are the model formulation for policy in developing Kauman tourist village. Such a policy model is expected to be able to become the pilot project of the development of the tourist villages not only in Surakarta city but also in other tourist cities in Indonesia in general through the implementation of eco-green tourism on the basis of the concept of green architecture which will not only conserve the tourism, cultural, and environmental assets, but also empower the prevailing local wisdoms.